Effect in vitro and in situ of proanthocyanidin-based dentifrices at the demineralized organic matrix submitted to erosion and dental abrasion - Bueno, Tamires de Luccas (2019)
The objective of this study was to evaluate, in vitro and in situ, the effect of experimental dentifrice based on Proanthocyanidin in the organic demineralized matrix after erosive and abrasive challenges. The in vitro portion of the study was performed using 50 dentin specimens obtained from bovine teeth (4x4x2 mm), randomly divided in five groups after microhardness test (ranging from:41) (N=10 per group): G1- placebo (negative control); G2- 0.012% chlorhexidine (1st positive control); G3- NaF 1110 ppm fluoride (2nd positive control); G4- 10% purified proanthocyanidin (1st test); G5- fluoride + proanthocyanidin (2nd test). Erosive challenge was performed using an acid beverage (Coca-cola®), 3x per day during 5min each, for 5 days. The abrasion challenge was performed after the first and third erosive cycles using a mechanical brushing simulator with 150g of load for 30s in each specimen covered with the respective dentifrice slurry. In between the erosive/abrasive challenges, specimens were stored artificial saliva. The in situ portion of the study followed a crossover, double-blinded, design, and was performed in 5 phases of 5 days each, with 10 healthy volunteers who wore 5 palatal devices (1 for each phase) with 4 dentin specimens each. As for the in vitro portion, dentin blocks were randomly divided into 5 groups and submitted to the same erosive challenges. For abrasive challenge, brushing was performed by the volunteers using an electric brush for 30s. For both in vitro and in situ portions, the profilometry was conducted at the initial and final time points, with five measurements for each period. In vitro data were analyzed using Kruskal- Wallis test, one-way ANOVA, following by Tukey test (p <0.05), and showed G4 and G5 with the lowest wear with median and Q1-Q3 of 0.48 (0.40-0.60) and 0.58 (0.55-0.62), respectively, followed by G3- 0.87 (0.74-1.03), G2- 1.25 (1.05-1.44), and G1- 1.68 (1.52-2.08). In situ data were analyzed by one-way ANOVA and Fishers LSD test (p <0.05), and showed similar trend of results: G4 and G5 showing the lowest wear 0.93 (± 0.38) and 0.82 (± 0.34) respectively, followed by G2 1.19 (± 0.42) and G3-1.29 (± 0.34), and G1- 1.76 (± 0.55) showing the highest wear. PA dentifrices and its combination with fluoride dentifrice can be an alternative to prevent mineral losses during erosive and abrasive challenges.